• Support PF! Buy your school textbooks, materials and every day products Here!

How to prove the following

  • Thread starter sajee3a
  • Start date
  • #1
1
0
1)given that: (1+x)^n=summation nCk X^K

PROVE: SUMMATION nCk p^k q^n-k =1, where p+q=1
2) prove the general law of addition: P(E1 U E2 U.....U En)=sum P(Ei)-sum P(EiEj)+sum P(EiEjEk)-.....(-1)^n-1 P(E1E2....En)
 

Answers and Replies

  • #2
mathman
Science Advisor
7,740
406
For 1:
1=(p+q)n=qn(1+(p/q))n=qnΣnCk(p/q)k=ΣnCkpkqn-k
 

Related Threads for: How to prove the following

  • Last Post
Replies
2
Views
1K
  • Last Post
Replies
3
Views
867
  • Last Post
Replies
1
Views
870
Replies
1
Views
3K
  • Last Post
Replies
5
Views
506
Replies
2
Views
635
  • Last Post
Replies
1
Views
3K
  • Last Post
Replies
12
Views
2K
Top